A coaching session framework to facilitate long-term athletic development - Till, K.; Eisenmann, J.; Emmonds, S.; Jones, B.; Mitchell, T.; Cowburn, I.; Tee, J.; Holmes, N.; Lloyd, R. S. (Strength and Conditioning Journal, 2021)
The implementation of long-term athletic development (LTAD) aims to improve health, physical activity, and performance of all youth. Contemporary LTAD models suggest that a broad range of physical and psychosocial competencies should be developed in youth, but few resources are available for coaches that describe "how" to achieve these outcomes. This article overviews a coaching session framework built around the following components: raise, activate, mobilize, prepare, activity, games, evaluate (RAMPAGE). The framework provides practitioners with information on what can be planned and delivered and when within a coaching session, across multiple ages and stages of development within multiple contexts (e.g., physical education and talent development).